If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -8 = 16 + 10 Reorder the terms: -8 + 6x = 16 + 10 Combine like terms: 16 + 10 = 26 -8 + 6x = 26 Solving -8 + 6x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 6x = 26 + 8 Combine like terms: -8 + 8 = 0 0 + 6x = 26 + 8 6x = 26 + 8 Combine like terms: 26 + 8 = 34 6x = 34 Divide each side by '6'. x = 5.666666667 Simplifying x = 5.666666667
| -2(x-1)=3x-18 | | 7+8n+5-3n= | | 3x-19=7x+17 | | 38+x+90=180 | | 2.3/18.4 | | 3(2+3K)+4(X-2)=5 | | 42=4y-14 | | 37+x+90=180 | | 30(10x-2)+x=56 | | -4z-2+8+5z= | | 86-x=266 | | 4(2x-3)+6=18 | | 38=2x-5y | | 5+3u=-1 | | 3(5x-9)=15x-27 | | 5x-7=7x-187 | | 2y+4=-2 | | 13=4m+7-m | | 7n-4+8n-3= | | 4.4q-3.7-5.5q=-0.1q-3.7 | | -19=5v+6 | | 0.08(y-8)+0.14y=0.18y-1 | | -14=-2+3v | | 6(6v+6)-5-6v=1 | | 5(x+6)=3(x+10)+2x | | (4x-4)+(3x+12)=0 | | 4x+x-6=5 | | 58=4x+10 | | -7(v+4)+4v+5=5v+11 | | 2(5r-9)= | | -3c-5-2c+6= | | 21x-11-12x=3(3x+5)+4 |